An Analysis Of Students Comprehension Level On Myob Accounting-Based Accounting Application (A Study In Accounting Students In Semarang Municipality) - Rinawati, Tri (Economics and Business Solutions Journal, 2017)
Accounting computerization students are taught to have accounting information system mindset, to apply, review, and develop the science underlying accounting information system engineering thoroughly. In addition to mastering several applications in accounting field, students also know how a software accounting works. Students of this department are taught to be experts in computer system be it software and hardware, particularly in accounting computer field.The population in this research is S1 and DIII students of Accounting department at universities and colleges in Semarang Municipality with some considerations. The sample is taken using Purposive Sampling. Meanwhile, the data are collected by distributing questionnaire. The data analysis method used is difference test with Independent Sampel t Test, where this test is employed to figure out whether or not there is a mean difference between two unrelated sample groups.There is indeed a difference in students comprehension on the initial data input, transaction recording and financial statements preparation. From the mean rank values of the three variables, it can be seen that students from Diploma program understand initial data input, transaction recording and financial statements preparation better than students from Bachelor program. This is because students from Diploma program receive more lessons on accounting both theoretically and practically, thus they understand the topics better.